Safety and efficacy of Lomecel‐B in patients with mild Alzheimer's disease: Results of a double‐blinded, randomized, placebo‐controlled phase 1 clinical trial. (31st December 2021) - Oliva, Anthony A.; Brody, Mark; Agronin, Marc; Herskowitz, Brad; Bookheimer, Susan Y; Hitchinson, Ben; Ramdas, Kevin; Wishard, Tyler; McClain‐Moss, Lisa; Diaz, Liliana A.; Yousefi, Keyvan; Perez, Carmen; et al.
Abstract: Background: Lomecel‐B is a formulation of allogeneic medicinal signaling cells (MSCs), which exert pleiotropic mechanisms of action (MOAs) with potential to simultaneously target multiple pathophysiological features of Alzheimer's disease (AD). Method: We conducted a double‐blinded, randomized, placebo‐controlled trial (ClinicalTrials.gov: NCT02600130). Mild AD patients (Table) were infused with Lomecel‐B at 20 (20M, N =15) or 100 million cells (100M, N =10), or placebo ( N =8). Eligibility screening included clinical evaluation, MRI to exclude other etiologies, and beta‐amyloid tracer PET to confirm AD. Scheduled follow‐ups were conducted through 1‐year post‐treatment. The primary endpoint was safety. Pre‐specified secondary endpoints evaluated efficacy in neurocognitive/neuropsychological, quality‐of‐life (QOL)/activities of daily living (ADL), and biomarker domains. Result: Lomecel‐B was well‐tolerated and did not trigger safety stopping rules, meeting the primary endpoint. Efficacy endpoints were improved in the Lomecel‐B groups. Whereas the Mini Mental State Exam (MMSE) declined in placebo by 2.99±1.12 points at Week 13 ( p =0.0337; 95%CI ‐5.84 – ‐0.31), the 20M Lomecel‐B group showed minimal decline (difference from placebo: 2.69±1.39 points; p =0.0182; 95%CI 0.51 – 4.97). This difference persisted over one year (Figure). On the QOL‐AD patient version, the 20M Lomecel‐B group significantly improved versus placebo at Week 26 by 3.85±1.94 points ( p =0.0444; 95%CI 0.13 – 9.12). On the ADCS‐ADL, the placebo group significantly declined at Week 26 by 9.27±2.78 points ( p =0.0211; 95%CI ‐17.83 – ‐2.10), and was significantly worse versus 20M Lomecel‐B by 6.95±3.46 points ( p =0.0118; 95%CI 1.99 – 13.94). In contrast, these assessments did not significantly differ in the 100M Lomecel‐B group versus placebo. Anti‐inflammatory (IL‐10, IL‐12, sIL‐2Rα) and pro‐vascular (VEGF, IL‐4, IL‐6) serum biomarkers were significantly higher in both Lomecel‐B groups versus placebo, with 100M Lomecel‐B generally showing the greatest rises. Left hippocampal volume increased in the 100M Lomecel‐B group versus placebo at Week 13 ( p =0.0311). Conclusion: These results support the safety and clinical potential of Lomecel‐B for AD. These hypothesis‐generating results also revealed potentially important biomarkers which are consistent with multiple MOAs of Lomecel‐B. Ongoing investigation of Lomecel‐B for AD in larger clinical trials powered for clinical efficacy is warranted. This study was supported through Alzheimer's Association Part the Cloud Challenge on Neuroinflammation grants #PTC C‐16‐422443 and PTC‐CS‐19‐623225.